Oxaliplatin as a radiosensitiser for upper and lower gastrointestinal tract malignancies: what have we learned from a decade of translational research? - Hill, E; Nicolay, N; Middleton, MR; Sharma, R (2012)
Some of the greatest advances in the treatment of solid malignancies have resulted from the combination of chemotherapy and radiotherapy treatments. This article comprehensively reviews the current clinical evidence for oxaliplatin-based chemo-radiotherapy that may improve local control and survival. In order to understand how clinical studies should be designed, the pre-clinical evidence for the use of oxaliplatin chemotherapy as a radiosensitising agent is appraised. Particular focus is placed on oxaliplatin's biological mechanisms of action, including cell cycle effects, the formation of DNA adducts and interstrand cross-links and the role of DNA repair proteins. At a clinical level, there is currently no evidence to suggest that oxaliplatin provides an additional benefit to concurrent chemo-radiation regimes that utilise fluoropyrimidines; we evaluate the reasons for this observation, the limitations of clinical trial design and the opportunities that currently exist to design clinical trials which are underpinned by an understanding of the basic biology.